f(3)=(-4)

Simple and best practice solution for f(3)=(-4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for f(3)=(-4) equation:



f(3)=(-4)
We move all terms to the left:
f(3)-((-4))=0
We add all the numbers together, and all the variables
f^3+4=0
We do not support efpression: f^3

See similar equations:

| 3r+4r-3r=12 | | p+2p-p=10 | | 3x^2+2x-65=0 | | 4x-5+5x+14=90 | | w+5w+2w+2w=20 | | Y=6,5x^2*5 | | 4(t–5.75)=65 | | z-z+3z+2z+2z=7 | | 6.908–g=0.173. | | 8n-6n=14 | | 4x-5+5x+14=180 | | 3(2p-1)=5(p+2) | | 4x-5=5x+14 | | 100,000=10n | | 1/(x-9)=6 | | 18(q-957)=108 | | 538-h=372 | | 12x+4x+2x=39 | | 54+9t=324 | | y=-(+2)+3 | | s+66/15=12 | | 10+5p=-20 | | y=2(-4)-5 | | 345=15(f-926) | | (x+15)^2=64x | | 2-4a=14=2a | | 101-3y=65 | | (x+15)²=64x | | y-1=3/5 | | 113-9n=32 | | s+233/25=13 | | 15x+5=-10x+25 |

Equations solver categories